154 SAFEGUARDING ADULTS AT RISK OF ABUSE—IDENTIFYING KNOWLEDGE GAPS AMONGST HOSPITAL STAFF TO GUIDE POLICY IMPLEMENTATION AND TRAINING. (18th November 2021) - Killeen, E; Higgins, M; Keogh, C; Russell, S; Curran, C
Abstract: Background: Safeguarding is the protection of health, wellbeing and life free from abuse. Abuse is a a violation of a person's human and civil rights; forms include psychological, financial, physical, sexual, neglect and self-neglect. Health Service Executive (HSE) drafted the 2019 'Adult Safeguarding Policy' for adults at risk of abuse to replace the 2014 version. In preparation for implementation a tertiary hospital founded a Safeguarding Committee in 2021. A core objective was establishing staff understanding, experience of safeguarding and education needs to guide future training. Methods: 10-question survey of 223 staff; included doctors, nurses, allied health professionals, medical social workers, healthcare assistants, porters, psychologists. Results: 91% response rate. 184 (91%) staff were familiar with the term 'safeguarding'; only 44% were aware of the HSE 2019 policy. 129 (64%) had experience with a case of suspected abuse. Most common forms were financial, psychological and self-neglect (n = 60, 47, 39 respectively). Sexual abuse was least common (n = 10). 47% felt 'somewhat' confident recognising possible abuse compared to 42% who felt 'extremely' or 'very' confident. 61% were 'somewhat' or 'not so' confident about the next steps for suspected abuse; only 11% were 'extremely' confident. 49% felt 'extremely' or 'very' confident in reporting a suspected abuse case; 50% felt 'somewhat' or 'not so' confident. Most common reasons for lack of confidence were lack of training, unclear reporting process and lack of experience with cases of abuse. Medical social workers were most confident; doctors were the least. 170 (84%) wanted more safeguarding training—the most popular options were online or in-person training. Conclusion: Gaps in knowledge and confidence were identified amongst staff for cases of suspected abuse. This will guide future training in the hospital in line with the HSE Adult Safeguarding policy.